Favorite dishes : a Columbian autograph souvenir cookery book. Over three hundred autograph recipes, and twenty-three portraits, contributed specially by the Board of lady managers of the World's Columbian exposition /: a Columbian autograph souvenir cookery book. Over three hundred autograph recipes, and twenty-three portraits, contributed specially by the Board of lady managers of the World's Columbian exposition. ([2012]) - Unknown
No abstract available